2017
DOI: 10.5897/ijlp2017.0371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different processing methods of soya beans (Glycine max) on its nutritive value and the performance of broilers: A qualitative selection approach for extension

Abstract: Several trials has been conducted by poultry nutritionist in evaluating effects of soybean processing on its nutritive value and the performance of broilers without clearly declaring the best processing method to be adopted by farmers that will give them on the average a cumulative best result output. A qualitative selection approach was thus adopted in the evaluation of different processing methods of soya beans (Glycine max) on its nutritive value and the performance of broilers using published results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Roasting (dry heating) involves heating soybeans at temperatures of 100 to 150°C for 30 minutes, while toasting involves heating soybeans at temperatures of 150 to 200°C for shorter time 30 minutes. Extrusion involves subjecting soybeans to high temperatures 140°C for 8 minutes, and pressures in an extruder, resulting in the denaturation of ANFs and improved digestibility of the protein (Rostagno et al, 2011;Ari et al, 2013Ari et al, , 2017Hemetsberger et al, 2022). Several studies have demonstrated the effectiveness of HT in reducing ANFs content in SBM.…”
Section: Heat Processing To Remove Anfs In Soybeanmentioning
confidence: 99%
“…Roasting (dry heating) involves heating soybeans at temperatures of 100 to 150°C for 30 minutes, while toasting involves heating soybeans at temperatures of 150 to 200°C for shorter time 30 minutes. Extrusion involves subjecting soybeans to high temperatures 140°C for 8 minutes, and pressures in an extruder, resulting in the denaturation of ANFs and improved digestibility of the protein (Rostagno et al, 2011;Ari et al, 2013Ari et al, , 2017Hemetsberger et al, 2022). Several studies have demonstrated the effectiveness of HT in reducing ANFs content in SBM.…”
Section: Heat Processing To Remove Anfs In Soybeanmentioning
confidence: 99%
“…Although they have high nutritional value, beans have some antinutritional compounds in their composition, which can reduce the digestibility of the nutrients present in the grain (Murube et al, 2021). In bean processing, contents of tannins and phytic acid are reduced or eliminated, influencing the nutritional characteristics of the grain, such as starch and protein digestibility (Adeleye et al, 2020; Ari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Soaking is an easy, low-cost treatment that can reduce the concentration of soluble antinutrients, which are eliminated with the soaking solution [ 14 ]. Alternatively, various heat methods, including cooking, microwaving, extrusion, toasting, and roasting, have been reported to be useful in decreasing the concentration and activity of heat-sensitive TIs [ 14 , 15 , 16 ]. Further, growth performance has been reportedly improved (higher body weight gain and lower feed conversion ratio) in broiler chickens that were fed heat-processed SB-containing diets, compared to those fed a raw soybean-containing diet [ 17 ], which could be due to an increase in nutrient availability following TI reduction.…”
Section: Introductionmentioning
confidence: 99%